Յովհաննէս Թումանեանի «Անուշ» պոեմը եւ Կոմիտասի համանուն անաւարտ օպերան - Վարդումեան, Արփի (տպ. Atlas)
The first version of the poem “Anush” by Tumanyan was published in 1892 in Moscow, in the second volume of his poems. As is well known, in the early 1900s, the author completely revised all his poems, including “Anush”. This collection was published in Tbilisi in 1903, and after reading it, Komitas had the idea of creating an opera based on the poem “Anush”. Komitas had received a fundamental musical education in Berlin, where he became acquainted with the principles of musical theater, the opera genre and the laws of classical opera. He decided to write an opera based on the poem “Anush”, since this plot most closely corresponded to his plan to create a truly folk vocal and musical work. He intended to subordinate the laws of classical opera to the spirit of Armenian folk musical thinking; in the end a new type of musical work would result, which might be a synthesis of these two styles. Unfortunately, Komitas’s plan remained unfinished, although there are more than 20 arias, duets, choral and orchestral parts from this opera.
Keywords: Արուեստ; Օպերա